2007
DOI: 10.3347/kjp.2007.45.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Tissue parasitic helminthiases are prevalent at Cheongjin, North Korea

Abstract: We investigated a small-scale serological survey to screen tissue-parasitic helminthiases of North Koreans as one of research programs for re-unification of Korea. Soil-transmitted helminthiases were found highly prevalent among North Korean residents at the border with China. ELISA using 4 tissue-parasitic helminth antigens was applied to 137 residents living in Cheongjin-shi, Hamgyeongbuk-do, North Korea and 133 female refugees in South Korea in 2004-2005. Among a total of 270 samples, 31 (11.5%), 25 (9.3%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…As shown in the results of this study, the majority of parasite positive cases were confirmed as T. trichiura infection. The high prevalence of trichuriasis in this study is in concordance with previous studies [ 4 , 5 ]. According to Lee et al [ 9 ], a refugee from NK diagnosed by colonoscopy was determined to have most probably been infected before leaving NK, as had been suffering the typical symptoms of intestinal helminthiasis while still living there.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…As shown in the results of this study, the majority of parasite positive cases were confirmed as T. trichiura infection. The high prevalence of trichuriasis in this study is in concordance with previous studies [ 4 , 5 ]. According to Lee et al [ 9 ], a refugee from NK diagnosed by colonoscopy was determined to have most probably been infected before leaving NK, as had been suffering the typical symptoms of intestinal helminthiasis while still living there.…”
supporting
confidence: 93%
“…Although some food-borne and zoonotic parasite infections along with malaria are still reported frequently, soil-transmitted parasites have been well controlled in South Korea [ 3 ]. Soil-transmitted helminthiases (STH), however, remain prevalent in some areas of North Korea (NK) and among North Korean refugees who manage to escape to the south [ 4 , 5 ]. Whereas a clear understanding of the health status of NK is mandatory for STH prevention and control measures, this objective is hampered by the lack of reliable data [ 6 ].…”
mentioning
confidence: 99%
“…Meat inspection of 6 seropositive pigs (6 infected) [ 39 ] na na + [ 21 ] Japan + [ 22 ] Laos Meat inspection of 590 pigs (5 infected) [ 10 ]. OIE reported cases occurring during 2005–2017 na na Meat inspection of 590 pigs (1 infected) [ 10 ] na Malaysia Mongolia OIE reported cases occurring during 2005–2017 na na Myanmar Meat inspection of 300 pigs (71 infected) [ 40 ] na na North Korea + [ 27 ] Philippines + [ 28 ] Singapore South Korea + [ 32 ] Thailand + [ 33 ] + [ 33 ] + [ 33 ] Vietnam Tongue examination of 172,087 pigs (109 infected) [ 41 ]. OIE reported cases occurring during 2005–2017 na na + [ 12 ] …”
Section: Resultsmentioning
confidence: 99%
“…To our best knowledge, only one article has attempted to explore this problem [25]. Out of 137 patients from a hospital in Cheongjin-shi, Hamgyeongbuk-do, DPRK, 27 were positive for clonorchiasis using ELISA test.…”
Section: Epidemiology Of Clonorchiasismentioning
confidence: 99%